Early Carboniferous synorogenic basins evolution of the Ossa-Morena and - Pereira, M Francisco (2017)
The stratigraphic record of the Early Carboniferous in Iberia reveals that synorogenic deposition was important and occurred simultaneously in basins influenced by extension and contraction with gravitational instability. In NW Iberia (Galicia – Trás-os-Montes Zone) contraction was dominant and the deposition took place in a forebulge outwards from the nappe stacking front. Here, synorogenic deposits were strongly affected by folding and thrusting as they were imbricated and incorporated in the allochthonous pile. In a different way, in SW Iberia (Ossa-Morena Zone) synorogenic deposition was influenced by extension and happened simultaneously with the onset of significant magmatism.